Metodologi Hukum Islam âAbd al-HalÃ®m MahmÃ»d - Ghozali, M. Lathoif (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This article discusses the concept of ijtihÃ¢d (legal reasoning) and the typology of legal thought of âAbd al-HalÃ®m MahmÃ»d. According to MahmÃ»d, ijtihad is devoting all abilities of a mujtahid to arrive at the essence and substance of a problem intended by the Prophet Muhammad. This definition is supported by the division of ijtihÃ¢d into two: ijtihÃ¢d istinbÃ¢tÃ®, the object of which is the texts of the QurâÃ¢n or the Sunnah, and ijtihÃ¢d tatbÃ®qÃ®, the object of which is legal problems of the time. Mahmud maintains that a mujtahid should meet certain qualifications such as the abilities of understanding Arabic language, memorizing the QurâÃ¢n, understanding asbÃ¢b al-nuzÃ»l (causes of revelation), memorizing the Traditions of the Prophet related to legal matters, and the brilliance in making legal reasoning and conclusions. MahmÃ»d belongs to moderate group that agrees with the formalization of private laws, while public laws in his view serve only as materials for national laws. MahmÃ»d also gives an emphasis on the integration between nass (text) and maqÃ¢sid al-sharÃ®âah (the objectives of law).